Dulaglutide versus insulin glargine in patients with type 2 diabetes and moderate-to-severe chronic kidney disease (AWARD-7): a multicentre, open-label, randomised trial. Issue 8 (August 2018) - Tuttle, Katherine R; Lakshmanan, Mark C; Rayner, Brian; Busch, Robert S; Zimmermann, Alan G; Woodward, D Bradley; Botros, Fady T
Summary: Background: Many antihyperglycaemic drugs, including insulin, are primarily cleared by the kidneys, restricting treatment options for patients with kidney disease. Dulaglutide is a long-acting glucagon-like peptide-1 receptor agonist that is not cleared by the kidneys, and confers a lower risk of hypoglycaemia than does insulin. We assessed the efficacy and safety of dulaglutide in patients with type 2 diabetes and moderate-to-severe chronic kidney disease. Methods: AWARD-7 was a multicentre, open-label trial done at 99 sites in nine countries. Eligible patients were adults with type 2 diabetes and moderate-to-severe chronic kidney disease (stages 3–4), with an HbA1c of 7·5–10·5%, and who were being treated with insulin or insulin plus an oral antihyperglycaemic drug and were taking a maximum tolerated dose of an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker. Participants were randomly assigned (1:1:1) by use of a computer-generated random sequence with an interactive response system to once-weekly injectable dulaglutide 1·5 mg, once-weekly dulaglutide 0·75 mg, or daily insulin glargine as basal therapy, all in combination with insulin lispro, for 52 weeks. Insulin glargine and lispro doses were titrated as per an adjustment algorithm; dulaglutide doses were masked to participants and investigators. The primary outcome was HbA1c at 26 weeks, with a 0·4% non-inferiority margin. Secondary outcomes included estimated glomerular filtration rate (eGFR) and urine albumin-to-creatinine ratio (UACR). The primary analysis population was all randomly assigned patients who received at least one dose of study treatment and had at least one post-randomisation HbA1c measurement. The safety population was all patients who received at least one dose of study treatment and had any post-dose data. This study is registered withClinicalTrials.gov, numberNCT01621178 . Findings: Between Aug 15, 2012, and Nov 30, 2015, 577 patients were randomly assigned, 193 to dulaglutide 1·5 mg, 190 to dulaglutide 0·75 mg, and 194 to insulin glargine. The effects on HbA1c change at 26 weeks of dulaglutide 1·5 mg and 0·75 mg were non-inferior to those of insulin glargine (least squares mean [LSM] −1·2% [SE 0·1] with dulaglutide 1·5 mg [183 patients]; −1·1% [0·1] with dulaglutide 0·75 mg [180 patients]; −1·1% [0·1] with insulin glargine [186 patients]; one-sided p≤0·0001 for both dulaglutide doses vs insulin glargine). The differences in HbA1c concentration at 26 weeks between dulaglutide and insulin glargine treatments were LSM difference −0·05% (95% CI −0·26 to 0·15, p<0·0001) with dulaglutide 1·5 mg and 0·02% (−0·18 to −0·22, p=0·0001) with dulaglutide 0·75 mg. HbA1c -lowering effects persisted to 52 weeks (LSM −1·1% [SE 0·1] with dulaglutide 1·5 mg; −1·1% [0·1] with dulaglutide 0·75 mg; −1·0% [0·1] with insulin glargine). At 52 weeks, eGFR was higher with dulaglutide 1·5 mg (Chronic Kidney Disease Epidemiology Collaboration equation by cystatin C geometric LSM 34·0 mL/min per 1·73 m 2 [SE 0·7]; p=0·005 vs insulin glargine) and dulaglutide 0·75 mg (33·8 mL/min per 1·73 m 2 [0·7]; p=0·009 vs insulin glargine) than with insulin glargine (31·3 mL/min per 1·73 m 2 [0·7]). At 52 weeks, the effects of dulaglutide 1·5 mg and 0·75 mg on UACR reduction were not significantly different from that of insulin glargine (LSM −22·5% [95% CI −35·1 to −7·5] with dulaglutide 1·5 mg; −20·1% [–33·1 to −4·6] with dulaglutide 0·75 mg; −13·0% [–27·1 to 3·9] with insulin glargine). Proportions of patients with any serious adverse events were similar across groups (20% [38 of 192] with dulaglutide 1·5 mg, 24% [45 of 190] with dulaglutide 0·75 mg, and 27% [52 of 194] with insulin glargine). Dulaglutide was associated with higher rates of nausea (20% [38 of 192] with dulaglutide 1·5 mg and 14% [27 of 190] with 0·75 mg, vs 5% [nine of 194] with insulin glargine) and diarrhoea (17% [33 of 192] with dulaglutide 1·5 mg and 16% [30 of 190] with 0·75 mg, vs 7% [14 of 194] with insulin glargine) and lower rates of symptomatic hypoglycaemia (4·4 events per patient per year with dulaglutide 1·5 mg and 4·3 with dulaglutide 0·75 mg, vs 9·6 with insulin glargine). End-stage renal disease occurred in 38 participants: eight (4%) of 192 with dulaglutide 1·5 mg, 14 (7%) of 190 with dulaglutide 0·75 mg, and 16 (8%) of 194 with insulin glargine. Interpretation: In patients with type 2 diabetes and moderate-to-severe chronic kidney disease, once-weekly dulaglutide produced glycaemic control similar to that achieved with insulin glargine, with reduced decline in eGFR. Dulaglutide seems to be safe to use to achieve glycaemic control in patients with moderate-to-severe chronic kidney disease. Funding: Eli Lilly and Company.